Primary micropapillary carcinoma of the colon with submucosal invasion: A case report - Miyaoka, Youichi; Fujiwara, Aya; Kotani, Satoshi; Tsukano, Kosuke; Ogawa, Sayaka; Yamanouchi, Satoshi; Kusunoki, Ryusaku; Fujishiro, Hirofumi; Kohge, Naruaki; Yamamoto, Tomohiko; Amano, Yuji (Endoscopy International Open, 2016)
Background and study aims: We present a case of invasive micropapillary carcinoma (IMPC) of the colon treated by endoscopic resection following magnifying endoscopy. A 47-year-old woman visited our hospital for follow-up of a positive fecal occult blood test. Colonoscopy revealed a semi-pedunculated reddish polyp, the surface of which showed gentle irregularity, and mild tension in the sigmoid colon. Magnifying colonoscopy with narrow band imaging revealed an irregular surface pattern with heterogeneity in vascular diameter and distribution. Magnifying endoscopic findings using crystal violet staining showed an irregular pit pattern with an expansion of stromal areas. Endoscopic resection of the sigmoid colon tumor was performed, and the histology of the resected specimen primarily revealed a micropapillary component with a small moderately differentiated adenocarcinoma component that massively invaded into the submucosal layer, accompanied by lymphatic invasion, although the tumor was very small (7 mm in diameter, smaller than any in previous reports). Laparoscopy-assisted sigmoidectomy and regional lymph node resection were performed; neither cancer nor lymph node metastases were present. This is the first report of a case with early-stage colonic IMPC observed with magnifying colonoscopy.